CHARACTERIZATION OF FOOD Athene cunicularia (STRIGIFORMES: STRIGIDAE) (BURROWING OWL) - Divaney Mamédio Dos Santos; Cordeiro, Verena Lima; Cardoso, Claus Burgos; Andrea, Maria Vanderly; Elinsmar Vitoria Adorno; Kaliane Nascimento De Oliveira (SciELO journals, 2018)
Abstract The aim of the proposal was to characterize the diet of Athene cunicularia by analysis of bezoars (regurgitation) in 15 burrows mapped in 10 acres campus UFRB in Cruz das Almas, Bahia. The regurgitations were subjected to treatments for identifying the percentage of each list item (vertebrates, invertebrates, plant material and stones). They were then subjected to treatments for identifying of items present. The analysis revealed that the feeding owls were composed of leaves, twigs, seeds, and many beetles and scarabaeidae lizard ameiva ossicles, and the presence of frogs (Bufo sp.) Without head and bone fragments rodents (Mus musculus, Rattus norvegicus and Rattus rattus). This power is varied under the influence of greater or lesser presence of people in the areas of the holes. By observation of behavioral attitudes, you can see that the parents have demonstrated protective action in relation to cub and burrows through the emission of sounds and overflights near the invaders.